Teacher Creativity in Reducing Learning Loafing on Fiqh Learning - Lestari, Surti; Hamdanah, Hamdanah; Surawan, Surawan (Program Magister Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2025)
Learning success is greatly influenced by a pleasant learning atmosphere. However, student laziness is often an obstacle that hinders the achievement of learning goals. Teachers' creativity in designing and implementing fun learning is essential to reduce student learning laziness, as well as support success in the learning process. This study aims to describe the form of teacher creativity in reducing student laziness in fiqh learning at MTs An-Nur Palangka Raya. This research is a type of qualitative research with a case study approach. Data collection techniques are carried out through observation, interviews, and documentation, as well as data validation techniques using triangulation of sources and techniques. The results of the study show that teachers' creativity in fiqh learning is able to effectively reduce students' lazy learning behavior. Teachers apply creativity through four main aspects, namely the ability to think fluently such as teachers explaining difficult material through examples in students' daily lives, high teacher teaching enthusiasm such as the use of loud voice intonation, changes in position in explaining, and body movements used in explaining material, flexible skills such as the use of varied learning methods and models, and the ability to think rationally such as the teacher's actions in solving problems that occur in the learning process. The implementation of this creativity is realized through the use of varied learning methods and models. Teachers' creativity is also evident from the way the material is delivered that is interactive, humorous, and contextual with students' lives. The application of these creative strategies has succeeded in increasing student participation, focus, and enthusiasm in the learning process.